University of Benin strategic plan, 2002-2012 - University of Benin (Benin City, Edo State, Nigeria : University of Benin, 2002)
Seeks to provide a comprehensive and unified guide for the University of Benin's development over a decade.
oif 18/07/2018
Loans
Keywords: University of Benin; Planning; Nigeria